2017
DOI: 10.1186/s40168-017-0313-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intrapartum antimicrobial prophylaxis upon the intestinal microbiota and the prevalence of antibiotic resistance genes in vaginally delivered full-term neonates

Abstract: BackgroundDisturbances in the early establishment of the intestinal microbiota may produce important implications for the infant’s health and for the risk of disease later on. Different perinatal conditions may be affecting the development of the gut microbiota. Some of them, such as delivery mode or feeding habits, have been extensively assessed whereas others remain to be studied, being critical to identify their impact on the microbiota and, if any, to minimize it. Antibiotics are among the drugs most frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
195
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 179 publications
(209 citation statements)
references
References 68 publications
13
195
0
1
Order By: Relevance
“…Furthermore, it has been suggested in studies of repeated faecal samples from term infants that the use of intrapartum PcV prophylaxis, to prevent early onset group B streptococcal infection in newborns, alters the offspring microbiome,48 49 although others have found very few differences between antibiotic-exposed and non-antibiotic-exposed infants 50. Meanwhile, maternal intake of probiotics influences the expression of toll-like receptors in infant meconium,51 indicating that fetal exposure of antibiotics may play an important role for the development of microbiota and the immune system of the child 48. While a causative association between antibiotics during pregnancy and VEO-IBD thus seems plausible, we cannot exclude possible confounding from an intrauterine infection with fever of the mother and a raised inflammatory reaction, causing epigenetic imprinting in the fetus and subsequent VEO-IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been suggested in studies of repeated faecal samples from term infants that the use of intrapartum PcV prophylaxis, to prevent early onset group B streptococcal infection in newborns, alters the offspring microbiome,48 49 although others have found very few differences between antibiotic-exposed and non-antibiotic-exposed infants 50. Meanwhile, maternal intake of probiotics influences the expression of toll-like receptors in infant meconium,51 indicating that fetal exposure of antibiotics may play an important role for the development of microbiota and the immune system of the child 48. While a causative association between antibiotics during pregnancy and VEO-IBD thus seems plausible, we cannot exclude possible confounding from an intrauterine infection with fever of the mother and a raised inflammatory reaction, causing epigenetic imprinting in the fetus and subsequent VEO-IBD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to vertical modes of transmission, the infant GIM may be continuously modified by environmental exposures; for example, maternal and/or infant antibiotic exposure is associated with a reduction in overall taxonomic richness and diversity of the infant GIM (Nogacka et al, ; Yasmin et al, ). Additionally, GIM composition may be influenced by pet ownership and proximity to animals (Azad et al, ; Tun et al, ), parental sanitation practices (pacifier cleaning method: Hesselmar et al, ; use of specific household products: Ribado et al, ) and other environmental factors varying by geographic location (Grześkowiak et al, ; Lin et al, ; Stearns et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that breast-milk or formula-milk provides a different recovery of the beneficial gut microbiota profile after its alteration by antibiotic exposure of babies or their mothers [35]. It is then necessary to elucidate the effect that the feeding type could play in the gut microbiota restoration of newborns after caesarean delivery.…”
Section: Perspectives and Future Trends On The Research About The Relmentioning
confidence: 99%